The Finnish Allergy Program 2008-2018: Society-wide proactive program for change of management to mitigate allergy burden - Haahtela Tari; Valovirta Erkka; Saarinen Kimmo; Jantunen Juha; Lindström Irmeli; Kauppi Paula; Laatikainen Tiina; Pelkonen Anna; Salava Alexander; Tommila Erja; Bousquet Jean; Vasankari Tuula; et al. (Mosby Inc., 2022)
A 10-year national program to improve prevention and management of allergic diseases and asthma was implemented in Finland (population 5.5. million) in 2008-2018. The main aim was to reduce the long-term burden of these conditions. The strategy was changed from traditional avoidance to tolerance and resilience of the population. Health was endorsed instead of medicalization of mild symptoms. Disease severity was reevaluated, and disabling clinical manifestations were given high priority. For health care, 5 quantitative goals and 1 qualitative goal were set. For each of the goals, specific tasks, tools, and outcome evaluation were stipulated. During the program, 376 educational sessions gathered 24,000 health care participants. An information campaign targeted the lay public, and social media was used to contact people. In the 10 years of the program, the prevalence of allergic diseases and asthma leveled off. Asthma caused fewer symptoms and less disability, and 50% fewer hospital days. Food allergy diets in day care and schools decreased by half. Occupational allergies were reduced by 45%. In 2018, the direct and indirect costs of allergic diseases and asthma ranged from €1.5 million to €1.8 million, with the 2018 figures being 30% less than in the respective figures in 2007. The Finnish proactive and real-world intervention markedly reduced the public health burden of allergic disorders. The allergy paradigm was revisited to improve management with systematic education.